2016
DOI: 10.4172/2161-0940.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ankle Intra-articular Injections

Abstract: Blind intra-articular injections (BIAI) of various joints are performed for diagnosis and treatments of different pathologies in sport medicine, rheumatology, general practice and orthopaedics. The gold standard for any joint injection is image guidance but studies have shown higher accuracy for BIAI. Objective of this study was to evaluate the intraoperative success and accuracy of ankle joint intra-articular injections. Materials and Methods: A total of 100 patients were assessed. Mean age was 34.11 years (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Lopes et al reported a blind ankle IAI accuracy rate of 77% in patients with rheumatoid arthritis [ 23 ]. Ramesh et al reported a blind ankle IAI accuracy rate of 63% when performed by orthopedic surgeons with different skill levels, including fellowship-trained foot and ankle specialists [ 58 ]. Heidari et al compared the blind ankle IAI accuracy rates of anteromedial and anterolateral approaches.…”
Section: Lower Extremitymentioning
confidence: 99%
“…Lopes et al reported a blind ankle IAI accuracy rate of 77% in patients with rheumatoid arthritis [ 23 ]. Ramesh et al reported a blind ankle IAI accuracy rate of 63% when performed by orthopedic surgeons with different skill levels, including fellowship-trained foot and ankle specialists [ 58 ]. Heidari et al compared the blind ankle IAI accuracy rates of anteromedial and anterolateral approaches.…”
Section: Lower Extremitymentioning
confidence: 99%